Stock-Bond Correlations In Asean-5: The Roles Of Financial Integration And Financial Development - Khalid, Muhammad Airil Syafiq Mohd (2020)
Based on Markowitz’s (1952) modern portfolio theory, studies of stock-bond correlation have gained considerable attention in academia as it explores the extent of asset diversification benefit between stock and bond markets. Existing literature has shown that the asset diversification benefit in developing countries are limited due to its high-country risk, making them less attractive as a destination for investment. In a related literature, countries that engaged in higher level of financial integration initiatives have been known to provide better asset diversification benefit. This study argues that such benefit may only exist in developed countries where country risk is low as opposed to developing countries where the countries risk is high. Hence, this study aims to examine the dynamic correlation between stock returns and changes in bond yields, SBcorr, in ASEAN-5 community and how it is affected by the level of financial integration in the period of 2007 - 2016. There are four stages of analyses in this study. The first two stages examine the level of stock market integration and SBcorr using DCC-MGARCH analysis. The third and fourth stages of analysis highlight the main objective of this study, whereby the impact of financial integration on SBcorr is examined using panel data and SUR estimations, respectively. Evidently, financial integration has a negative impact on SBcorr, implying low diversification benefit, contradicting most past findings. The study contends that financial integration alone cannot provide higher diversification benefit as both stock and bond returns in ASEAN-5 are highly correlated due to high country risks.